Graphene-based electrocatalysts for advanced energy conversion - Pingping Yang; Xin Yang; Wenzhu Liu; Ruike Guo; Zufu Yao (Green Energy & Environment, 2023)
Graphene-based nanocatalysts have appealed much interest as advanced electrocatalysts toward energy conversion reactions due to their outstanding electrocatalytic performance from the distinctive chemical composites and strong synergistic effects. Aiming to better understand the role of graphene played in enhancing the catalytic performance and offer guidance for fabricating more efficient graphene-based electrocatalysts, we herein summarize the remarkable achievements of graphene-based electrocatalysts for energy-conversion-related reactions. Started by discussing applications of graphene in the electrocatalytic reactions, we have manifested the crucial role of graphene played in promoting the catalytic performance. Subsequently, many representative graphene-based catalyst hybrids for electrocatalytic reactions are also overviewed, showing many effective strategies for the fabrication of more efficient graphene-related materials for the practical application. Finally, the perspective insights and challenging issues are also concluded to provide directions for the future development.